Relationship between Financial Literacy and Student’s Stock Market Participation - Acharya, Aaditya; Hamal, Janga Bahadur (Nepalese Journal of Business and Management Studies, 2022)
Many studies have investigated the relationship between financial literacy and stock market participation. However, there are limited studies regarding the association between students’ financial literacy level and stock market participation in Nepal. So, the study is aimed to discover the relationship between students’ financial literacy level and their stock market participation. The study has explored gender as moderating variable. The independent variable: financial literacy is further classified into basic financial literacy and advance financial literacy, whereas the dependent variable is stock market participation. For data collection, a structured questionnaire was distributed among 144 students, out of which 134 students represent the sample size. Undergraduate students of ward 16 of Kathmandu metropolitan city were the study population, which is 3,040. Thus, the required sample size was only 97 using the Yamane equation. The descriptive and relational research designs were used in the study. The statistical tools used for data analysis were Mann- Whitney U test, and Spearmen rank correlation analysis. The finding concludes that financial literacy level and student’s stock market participation are positively associated with each other. Further, the finding shows that gender has no moderating effect on financial literacy level but has a significant effect on stock market participation level